The role of termite CH4emissions on the ecosystem scale: A case study in the Amazon rainforest - Asperen, Hella L. van; Alves-Oliveira, João Rafael; Warneke, Thorsten; Forsberg, Bruce Rider; Araújo, Alessandro Carioca de; Notholt, Justus (Biogeosciences, 2021)
The magnitude of termite methane (CH4) emissions is still an uncertain part of the global CH4budget and current emission estimates are based on limited field studies. We present in situ CH4emission measurements of termite mounds and termite mound subsamples performed in the Amazon rainforest. Emissions from five termite mounds of the species Neocapritermes brasiliensis were measured by use of a large flux chamber connected to a portable gas analyser measuring CH4and CO2. In addition, the emissions of mound subsamples were measured, after which the termites were counted so that a termite CH4and CO2emission factor could be determined. Mound emissions were found to range between 17.0 and 34.8 nmol mound-1s-1for CH4and between 1.1 and 13.0 μmol mound-1s-1for CO2. A termite emission factor of 0.35 μmolCH4g-1termite h-1was found, which is almost twice as high as the only other reported value for the Amazon. By combining mound emission measurements with the termite emission factor, colony sizes could be estimated, which were found to range between 55-125 thousand individuals. Estimates were similar to literature values, and we therefore propose that this method can be used as a quick non-intrusive method to estimate termite colony size in the field. The role of termites in the ecosystem's CH4budget was evaluated by use of two approaches. Termite mound emission values were combined with local mound density numbers, leading to an estimate of 0.15-0.71 nmolCH4m-2s-1, on average, emitted by termite mounds. In addition, the termite CH4emission factor from this study was combined with termite biomass numbers, resulting in an estimate of termiteemitted CH4of ~ 1.0 nmolm-2s-1. Considering the relatively low net CH4emissions previously measured at this ecosystem, we expect that termites play an important role in the CH4budget of this terra firme ecosystem. © 2020 Institute of Electrical and Electronics Engineers Inc.. All rights reserved.
Keywords: Isoptera; Neocapritermes